Investigation of the Relationship Between Digital Game Addiction, Peer Relationships and Leisure Time Activity Level in Early Adolescence - Sezer, Mustafa; Cengiz, Ömer (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2025)
In this study, it was aimed to measure the relationships between digital game addiction, peer relationships and leisure time activity level in early adolescence. The sample of the study consisted of 413 students obtained on the basis of volunteerism by simple random sampling method from 6th and 8th grade students of Koç Secondary School in the 2021-2022 academic year. The data were obtained by combining the ‘digital game addiction’, ‘peer relations’ and ‘leisure time activity level’ scales with demographic questions. Relational screening model was established and the data were evaluated with SPSS 22 package programme. In the findings obtained, while the level of leisure time activity did not differ significantly according to gender, a difference was determined in favour of boys in digital game addiction. In peer relationships, a significant difference was observed in the sub-dimensions of protection, closeness and help in favour of girls. No significant difference was found between leisure time activity level and digital game addiction. There was a negative relationship between age and leisure time activity level, digital game addiction and peer relationships. While leisure time activity level positively and significantly affected peer relationships, there was no significant relationship between leisure time, peer relationships and digital addiction. As a result, it was determined that there is a relationship between digital game addiction, peer relationships and leisure time activity level in early adolescence.